Incidence of perioperative delirium at the hospital nacional arzobispo loayza, october to December 2021, Lima Peru: Incidencia de delirium perioperatorio en el Hospital Nacional Arzobispo Loayza, octubre a diciembre 2021, Lima Perú - Siu Wong, Carlos G. (2022)
OBJECTIVE: To determine the incidence of perioperative delirium (POD) at the Hospital nacioanl Arzobispo Loayza, from October to December 2021.   METHODS: Qualitative and prospective observational study, carried out in a population of 910 patients, in which the AMT Test Confusion Assessment Method (CAM) and the Pfeiffer questionnaire (Short Portable Mental Status Questionnaire, SPMSQ) were applied. We used Chi2 to demonstrate the existence of association and Cramer's V and Phi tests to quantify the intensity of said relationship if it existed.   RESULTS: Of the total of patients (910), 18.46% presented perioperative delirium. Sex and religion do not influence this. Age does influence the presentation of POD since 50% (145) of the patients 61 years of age or older presented it, unlike those between 36 -60 years of age only 5.31% and those of 18 - 35 only 0.88% presented POD. According to the level of education: 100% with no education, 73.1% with primary education, 18.5% with secondary education  and 5.8% with higher education, presented DPO. According to the anesthetic technique, POD was found in 28.9% (60) of the spinal type with sedation, 22.4% (11) of the epidural type with sedation, 16.7% (83) of the General TIVA TCI type, 12.9% (4) of the Block type with sedation, 9.5% (10) of the General balanced type; for the types of general anesthesia manual TIVA, General Multimodal and Spinal anesthesia without sedation there were no cases of POD. According to the operative time: 100% (9) of the patients with more than 6 hours of operative time, 27.1% (38) of the patients who have 3 to 6 hours of operative time and 16.5% (121) of the patients who have 1 to 3 hours of operative time presented cases of POD.   According to hospitalization time prior to surgery: 48% (36) of patients with hospitalization time of 16 to 30 days, 20.5% (26) of patients with hospitalization time of 8 to 15 days and 16% (97) of the patients with hospitalization time of 3 to 7 days presented POD. According to the presence of comorbidities: 51.6% (16) with AHT and RD, 41.7% (30) with Diabetes and 40.8% (20) with AHT and DM2 present POD.     According to the presence of dementia: 100% (6) of the patients with a history of dementia and 17.9% (162) of the patients with no history of dementia presented POD. According to psychiatric history, 68.4% (13) of those who did have a history of psychiatric disorder and 17.4% (155) of those who did not have a history of psychiatric disorder presented POD. According to history of psychiatric treatment: 100% (6) of those who do have a history of treatment and 17.9% (162) of those who do not have a history of psychiatric treatment presented POD. According to the pre-surgical and post-surgical PFEIFFER questionnaire: 100% of those with mild, moderate or severe cognitive impairment according to the PFEIFFER PRE QX questionnaire presented POD. According to diagnosis of pre-surgical and post-surgical delirium: 100% presented POD.   CONCLUSIONS: There is no association between sex and religion and the presentation of POD. If there is an association between age, educational level, type of anesthesia, operative time, hospitalization time prior to surgery, comorbidities, history of dementia, history of psychiatric disorder, history of psychiatric treatment, pre-, post-surgical Pfeiffer questionnaire, pre-surgical delirium and post-surgical delirium and the presentation of POD,